2021
DOI: 10.1080/10717544.2021.1921073
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of the efficacy and safety of human lung-targeting liposomal methylprednisolone crosslinked with nanobody

Abstract: Glucocorticoid (GC) hormone has been commonly used to treat systemic inflammation and immune disorders. However, the side effects associated with long-term use of high-dose GC hormone limit its clinical application seriously. GC hormone that can specifically target the lung might decrease the effective dosage and thus reduce GC-associated side effects. In this study, we successfully prepared human lung-targeting liposomal methylprednisolone crosslinked with nanobody (MPS-NSSLs-SPANb).Our findings indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The particle size distribution of MPS-NSSLs was 95.4 ± 0.7 nm, the encapsulation rate of MPS reached 91.24 ± 0.27 %, and the drug-to-lipid ratio was about 0.4. The rat model experiments confirmed that MPS-NSSLs had specific targeting and good stability, which was consistent with the results of Weng et al (2021) (27). There are other reports (28)(29)(30)(31) in this regard.…”
Section: Discussionsupporting
confidence: 91%
“…The particle size distribution of MPS-NSSLs was 95.4 ± 0.7 nm, the encapsulation rate of MPS reached 91.24 ± 0.27 %, and the drug-to-lipid ratio was about 0.4. The rat model experiments confirmed that MPS-NSSLs had specific targeting and good stability, which was consistent with the results of Weng et al (2021) (27). There are other reports (28)(29)(30)(31) in this regard.…”
Section: Discussionsupporting
confidence: 91%
“…35 Because they possess many desirable attributes, such as small molecules, low immunogenicity, strong penetration, and high binding affinity, different types nanobodies have become novel diagnosis and treatment methods for tumors and infectious diseases. [36][37][38] We constructed a nanobody specific to dectin 1, which is an important PRR in fungal infection. We also verified that this nanobody can bind to the dectin 1 antigen and relieve the inflammatory response in fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of glucocorticoid-like methylprednisolone lowered the expression of NF-kappa B due to its anti-inflammatory properties in rats with bleomycin-induced ALI. Furthermore, this group also elucidated on the targetability of these NPs to specifically bind to human lung tissue but not to the human spleen, liver, and kidney tissues [ 86 ]. Wijagkanalan et al .…”
Section: Nanoparticles Targeting Macrophages For Ards/alimentioning
confidence: 99%